Self-awareness protects working memory in people under chronic stress: An ERP study - Xing, Wenjuan; Zhang, Shu; Wang, Zheng; Jiang, Dan; Han, Shangfeng; Luo, Yuejia (Frontiers in Psychology, 2022)
Abstract: Chronic stress impairs working memory (WM), but few studies have explored the protective factors in the impairment. We aimed to investigate the effect of self-awareness on WM processing in people under chronic stress. Participants under chronic stress completed an n-back task after a self-awareness priming paradigm or a control task, during which electroencephalograms were recorded. The behavioral results showed that participants whose self-awareness was primed reacted faster and more accurately than the controls. Event-related potentials (ERPs) revealed that (1) P2 was more positive in the self-awareness group compared with the controls, indicating that self-awareness enhanced allocation of attention resources at the encoding stage. (2) N2 was attenuated in the self-awareness group compared with the controls, indicating that smaller attention control efforts are required to complete WM tasks adequately after priming self-awareness. (3) Enhanced LPP was evoked in the self-awareness group compared with the controls, suggesting self-awareness enables participants to focus attention resources on the information at the maintenance stage. Critically, mediational analyses showed that LPP mediated the relationship between self-awareness and WM response times. This result reflects the fact that priming self-awareness achieves better behavioral performances which may be attributed to sustained attention resources mobilization at the maintenance stage. In sum, self-awareness exerts a protective effect on WM in those under chronic stress, which may be due to the enhancements in allocation and mobilization of attention. These results could be used to develop more specific coping strategies for people under chronic stress.